Patterns of Etruscan Urbanism - Stoddart, Simon; Palmisano, Alessio; Redhouse, David; Barker, Graeme; di Paola, Giorgia; Motta, Laura; Rasmussen, Tom; Samuels, Troy; Witcher, Robert (Frontiers in Digital Humanities, 2020)
This paper examines the patterns of Etruscan urbanism by the innovative use of newly available rural data, employing rank size, and indices of centralization. The detailed case study looks at the development of urbanism of pre-Roman Etruria where both robust and delicate urbanism were present alongside one another. To achieve this end, the paper will draw on the complementary features of two recent articles—Redhouse and Stoddart (2011) and Palmisano et al. (2018)—to provide a synthesis that both examines the large places and the supporting rural settlement. The territorial boundaries of the major urban places were predicted by the XTENT model in the first article. The cumulative numbers of rural settlement (and other proxies of population) over time were examined in the second article. This paper will look at the regional variation in landscape organization within the predicted territorial boundaries of the major robust centres and the more delicate transitory centres, as well as the buffer zones in between. At least three phases of boundary development can be examined, equivalent broadly to the Iron Age, Orientalizing/Archaic and Post Archaic periods, seeking to match these with the correspondingly dated rural settlement. The results will be critically examined in terms of broader knowledge of the economic and political development from current fieldwork in Etruria. The ethnographic analysis of Kopytoff (1989) will also be applied to assess the application of the internal African frontier to the central Italian context. In this way, the quantitative will be matched with the qualitative to provide a deeper understanding of urban development in an under-assessed example within the Mediterranean world.